2016
DOI: 10.3389/fmicb.2016.01947
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of rpoB Mutations with Minimal Inhibitory Concentration of Rifampin and Rifabutin in Mycobacterium tuberculosis in an HIV/AIDS Endemic Setting, South Africa

Abstract: Treatment of tuberculosis (TB) and HIV co-infections is often complicated by drug-to-drug interactions between anti-mycobacterial and anti-retroviral agents. Rifabutin (RFB) is an alternative to rifampin (RIF) for TB regimens and is recommended for HIV patients concurrently receiving protease inhibitors because of reduced induction of CYP3A4. This study sought to determine the proportion of RFB susceptible isolates among RIF-resistant strains in a high HIV prevalence setting in South Africa. In addition, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…The data of Jing et al ( 2017 ) also emphasize the use of RFB in the place of RIF because MIC for all of the resistant isolates exhibited lower RFB MIC compared with RIF. The data are consistent with previous findings (Jamieson et al, 2014 ; Berrada et al, 2016 ), which have demonstrated that the rpoB mutations S531L, H526D, H526R, H526C, and D516V confer phenotypical high-level resistance to both RIF and RFB; amino acid substitution at codons L511P, D516G/Y, S522L, H526Y/L/D/N, S531Q, and L533P was associated with phenotypic resistance to RIF and susceptibility to RFB (Rukasha et al, 2016 ). Roughly 5% of cases of Mtb resistance to RIF did not exhibit any mutation in the rpoB gene, suggesting some alternative mechanism for RIF resistance or a mutation in another part of the rpoB gene.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The data of Jing et al ( 2017 ) also emphasize the use of RFB in the place of RIF because MIC for all of the resistant isolates exhibited lower RFB MIC compared with RIF. The data are consistent with previous findings (Jamieson et al, 2014 ; Berrada et al, 2016 ), which have demonstrated that the rpoB mutations S531L, H526D, H526R, H526C, and D516V confer phenotypical high-level resistance to both RIF and RFB; amino acid substitution at codons L511P, D516G/Y, S522L, H526Y/L/D/N, S531Q, and L533P was associated with phenotypic resistance to RIF and susceptibility to RFB (Rukasha et al, 2016 ). Roughly 5% of cases of Mtb resistance to RIF did not exhibit any mutation in the rpoB gene, suggesting some alternative mechanism for RIF resistance or a mutation in another part of the rpoB gene.…”
supporting
confidence: 92%
“…Rifabutin (RFB), a member of rifamycin family, was approved by the FDA in 1992 and was recognized in 2009 as an essential medicine by WHO (World Health Organization, 2011 ; Crabol et al, 2016 ). Rifabutin is recommended for tuberculosis (TB) [including Mycobacterium avium complex (MAC)] treatment and has been used in patients coinfected with HIV/AIDS (Rukasha et al, 2016 ). Rifabutin exhibits fewer drug-drug interactions than rifampicin (RIF) and induces cytochrome P450 (CYP 3A4 ) to a much lower degree than RIF (Zhang et al, 2011 ; Dutta and Karakousis, 2015 ).…”
mentioning
confidence: 99%
“…The lower specificity of RIF can be explained by the “disputed” mutations H526Y (7 isolates) and H526D (3 isolates) which confer low level RIF resistance and are often classified as susceptible by phenotypic DST methods especially the MGIT 960 assay [ 6 , 7 ]. These mutations are endemic in our setting and have been reported in significant numbers (8–20%) by researchers in South Africa and other countries [ 8 10 ]. The WHO recommends solid media for DST of RIF in strains harboring disputed mutations.…”
Section: Discussionmentioning
confidence: 87%
“…Knowing the exact mutation is crucial, as resistance is not a binary phenomenon and different mutations that are identified by this assay confer a range of resistance phenotypes with large variations in MICs (15)(16)(17)(18). Five disputed rpoB mutations (17,22,24,25). Similarly, infections caused by strains harboring mutations in the promoter region of inhA may still be treated with high-dose isoniazid (26,27).…”
Section: Discussionmentioning
confidence: 99%